Electronic and crystal structure and bonding in Ti-based ternary solid solution nitrides and Ti–Cu–N nanocomposite films - Patsalas, Panos; Abadias, Gregory; Koutsokeras, Loukas E. (My University, 2010)
Complex transition metal nitrides (TMN) have lately gained special attention in an effort to improve the properties of their binary counterparts. In this work we review a very wide range of binary and ternary transition metal nitrides of the form: TixTM1 − xN (TM = Zr,Hf,Nb,Ta,Mo,W) over the whole composition x range (0 < x < 1) grown by Pulsed Laser Deposition (PLD), Dual Ion Beam Sputtering (DIBS) and Magnetron Sputtering (MS). We identify the bonding mechanism and, despite the possible different valence electron configuration of the constituent elements, we show that TMNs are completely soluble to each other due to the hybridization of the d and sp electrons of the metals and nitrogen, respectively. Optical absorption bands are manifested due to the N-p → Me-d interband transition and the t2g → eg transition due to splitting of the metals’ d band, proving the partial ionic character of the bonds in TMNs. In addition, we consider the growth of Ti–Cu–N nanocomposites by PLD and MS. We investigate the difference in the atomic structure and bonding in both cases of ternary and nanocomposite nitrides, for sequential deposition of Ti and TM or Cu (achieved in PLD) or simultaneous deposition (achieved in DIBS, MS) and get insights for the kinetic effects
Keywords: Bonding; Physical vapor deposition; Structure; Ternary nitrides